MAIZE STALK SUSTAINABILITY IN MAIZE HYBRIDS FROM DIFFERENT ERAS AS AFFECTED BY PLANT DENSITY - Sangoi, Luís; Almeida, Milton Luiz de; Gracietti, Marcos Antônio; Bianchet, Paula; Horn, Delson (Revista de Ciências Agroveterinárias, 2002)
The increment in plant density enhances the radiation interception period by maize. Nonetheless, it also stimulates etiolation, favoring root and stem lodging. This experiment was conducted aiming to evaluate the effects of population density on plant architecture, stalk sustainability and grain yield of maize hybrids from different eras. The experiment was installed in Lages, SC, on 10/20/2000. A split plot design was used. Hybrids Agroceres 12 (Ag 12), Agroceres 303 (Ag 303) and Dekalb 929 (DKB 929), commercially released in the 70’s, 80’s and 90’s, respectively, were tested in the main plots. Plant populations equivalent to 25,000, 50,000, 75,000 and 100,000 pl ha-1 were assessed in the split plots. Morphological and allometric traits, root and stem lodging, grain production of erect and prostrated plants were determined. Plant population density did not affect root lodging. The increase in plant number per hectare from 25,000 to 100,000 stimulated greater stalk lodging for hybrids Ag 12 and Ag 303, but did not interfere with DKB 929 stem sustainability. Traits such as low ear-to-plant height ratio and high stem diameter homogeneity were instrumental to mitigate DKB 929’s stalk lodging before harvesting. Maize stem sustainability is fundamental to properly explore commercial hybrids yield potential through the use of high plant populations.